2022
DOI: 10.1029/2021jd036282
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Arctic Sea Ice Concentration on Extended‐Range Prediction of Strong and Long‐Lasting Ural Blocking Events in Winter

Abstract: It is traditionally considered that the predictability of atmosphere reaches approximately 2 weeks due to its chaotic features. Considering boundary conditions, the lead prediction time can exceed 2 weeks in certain cases. We find that the Arctic sea ice concentration (SIC) is crucial for extended‐range prediction of strong and long‐lasting Ural blocking (UB) formation. By applying the rotated empirical orthogonal function‐based particle swarm optimization algorithm, the conditional nonlinear optimal perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 62 publications
6
23
0
Order By: Relevance
“…We note that the positive SLP anomaly pattern at lag −3 is very similar to Ural blocking (e.g. Luo et al 2016, 2017, Yao et al 2017, Peings 2019, Ma et al 2022, which has been treated as an important internal atmospheric variability in winter. To represent such a prior atmospheric circulation forcing, we projected daily anomalous SLP fields onto the positive SLP anomaly pattern at lag −3 (figure S4(a), the projected subarctic Eurasian area spanning 30 • -90 • N, 0 • -140 • E) to obtain the atmospheric forcing index I atm (figure S4(b)).…”
Section: Observed Lead-lag Relationship Between Bk Sea Ice and Atmosp...mentioning
confidence: 52%
“…We note that the positive SLP anomaly pattern at lag −3 is very similar to Ural blocking (e.g. Luo et al 2016, 2017, Yao et al 2017, Peings 2019, Ma et al 2022, which has been treated as an important internal atmospheric variability in winter. To represent such a prior atmospheric circulation forcing, we projected daily anomalous SLP fields onto the positive SLP anomaly pattern at lag −3 (figure S4(a), the projected subarctic Eurasian area spanning 30 • -90 • N, 0 • -140 • E) to obtain the atmospheric forcing index I atm (figure S4(b)).…”
Section: Observed Lead-lag Relationship Between Bk Sea Ice and Atmosp...mentioning
confidence: 52%
“…(2020), and Ma et al. (2022). There is one difference from previous studies according to the research objective, which is the initial perturbation.…”
Section: Experimental Design For Acquiring the Cnopmentioning
confidence: 96%
“…In other words, the CNOP-type initial uncertainties among the three cases may be similar if the objective function is only measured by the high-pressure or low-pressure changes. Such a deduction is based on the results of Ma et al (2022), in which the objective function is defined by the Ural blocking index and the CNOPs are similar among different cases. However, this conjecture needs to be further examined in future work.…”
Section: Cnop-type Initial Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…He et al (2020) showed that Ural blockings and Eurasian below-average temperatures were likely more frequent in winters with deep Arctic warming than shallow, nearsurface warming over the BKS. Ma et al (2022) found that SIC perturbations in the Greenland Sea, Barents Sea and Okhotsk Sea in winter were important for extended-range prediction of the strong and long-lasting Ural blocking formation, where negative (positive) SIC perturbations favored (inhibited) the Ural blocking formation four pentads later. Zhang R et al (2018) suggested that heavy (light) SIC in the Barents Sea in spring-summer favored more frequent (rare) Ural blocking in summer.…”
Section: Introductionmentioning
confidence: 95%